Secure E-Voting System Utilizing Fingerprint Authentication, AES-GCM Encryption and Hybrid Blind Watermarking - Asia Abdullah; Nada Hussein M. Ali (Journal of Applied Engineering and Technological Science (JAETS), 2025)
Ensuring security, integrity, and reliability of the election process consider as the main challenges in the electronic voting system. This paper describes the e-voting system by integrating the biometric authentication, advanced encryption, and watermarking techniques towards meeting such challenges. The system employs the fingerprint authentication by utilizing the Scale-Invariant Feature Transform (SIFT) for verifying the identity of the voter to ensure genuineness and non-repudiation of the service. The vote will be encrypted with the AES-GCM technique to be employed in securing the voting process, thus ensuring both data privacy and integrity. Hybrid Blind Watermarking employs the technique of Discrete Wavelet Transform (DWT) and Discrete Cosine Transform (DCT) for embedding the encrypted vote into the colored watermark cover image. Increased robustness against attacks with maintained vote confidentiality is achieved through this approach. The experimental results proved its imperceptibility to reach a Peak Signal-to-Noise Ratio (PSNR) of 40.7 and Normalized Correlation (NC) of 1. Thus, the proposed system enhances the theoretical foundation of secure e-voting and provides an implementation strategy for a reliable and tamper-proof voting system.